2003
DOI: 10.1176/jnp.15.2.130
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Memory Stimulation Programs in Alzheimer's Disease

Abstract: The authors describe the memory stimulation programs used in the treatment of Alzheimer's disease (AD) and review their efficacy. Visual imagery, errorless learning, dyadic approaches, spaced retrieval techniques, encoding specificity with cognitive support at retrieval, and external memory aids were the memory stimulation programs used alone or in combination in AD. Preliminary evidence suggests that the errorless learning, spaced retrieval, and vanishing cues techniques and the dyadic approach, used alone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(30 citation statements)
references
References 78 publications
1
27
0
2
Order By: Relevance
“…Despite the uncertainty about the exact nature of the collaborative advantage, this study supports the claim made by Quayhagen and Quayhagen (2001) that cognitive rehabilitation for persons with dementia benefits from active participation of caregivers (see also De Vreese, Neri, Fioravanti, Belloi, & Zanetti, 2001;Grandmaison & Simard, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Despite the uncertainty about the exact nature of the collaborative advantage, this study supports the claim made by Quayhagen and Quayhagen (2001) that cognitive rehabilitation for persons with dementia benefits from active participation of caregivers (see also De Vreese, Neri, Fioravanti, Belloi, & Zanetti, 2001;Grandmaison & Simard, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…A number of studies have shown that increasing cognitive support can attenuate the memory losses associated with normal aging (Bäckman & Small, 1998) and disease-related declines (Bäckman & Small, 1998;Herlitz et al, 1992). This has stimulated the development of intervention programs designed to assist those with failing memory (Grandmaison & Simard, 2003).…”
Section: Cognitive Support and Memorymentioning
confidence: 99%
“…Although the memory impairment and atrophy are less severe in MCI-A than in AD, these alterations clearly indicate that there is a cognitive and biological rationale supporting the utilisation of similar cognitive training techniques in MCI-A and AD. Therefore, the selection of techniques such as errorless (EL) learning and spaced retrieval (SR), that have shown good preliminarily efficacy in AD (for reviews see Grandmaison & Simard, 2003;Sitzer, Twamley, & Jeste, 2006), seem well-justified in MCI-A. Briefly, EL consists of reducing or eliminating errors during the encoding phase (Wilson, Baddeley, Evans, & Shiel, 1994), whereas SR aims at gradually increasing intervals between recalls (Camp, 1989;Camp & McKitrick, 1992), thus facilitating retrieval.…”
Section: Introductionmentioning
confidence: 99%